Self-adaptive heat extraction controller for solar thermal tower operational with molten salt tanks - Ahmed, Farooq; Guanghua, Lyu; Akram, Farah; Hussain, Fida; Hussain Shah, Syed Hadi; Soomar, Arsalan Muhammad; Kamel, Salah (Frontiers in Energy Research, 2023)
Molten salts are commonly used in solar thermal power plants to store heat when sunlight is unavailable. However, solidifying the salts can lead to operational interruptions and prevent an optimal energy output. A self-adaptive heat extraction method has been proposed to regulate salt pipeline temperatures, enabling continuous operations that mitigate unplanned shut-downs. Such a method focuses on maintaining operational temperatures and preventing interferences caused by the freezing of the salts. The proposed Self-Adaptive Heat Extraction Controller (SAHEC) relies on fuzzy logic integrated into MATLAB Simulink to ensure optimal heat extraction control utilizing four distinct temperature variables. Modeling this approach through a created MATLAB-based simulation reveals that SAHEC offers an undeniable improvement over standard conventional methods for manipulating temperatures.